PENGARUH E-COMMERCE SHOPEE TERHADAP POLA KONSUMSI MAHASISWA UNIVERSITAS NU SIDOARJO - Lailatul Musfiroh; Dina Agustianingsih; Muhammad Farly Rizky (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to examine the influence of Shopee's E-Commerce Facilities (Features) on the consumption patterns of students at Universitas NU Sidoarjo. Data collection was conducted using a questionnaire method targeting students of Universitas NU Sidoarjo who actively use the Shopee application, with purposive sampling employed as the sampling technique. To analyze the data, IBM SPSS Statistics version 26 was utilized, employing a simple linear regression method. The findings reveal that Shopee's E-Commerce features significantly impact students' consumptive behavior. This is evidenced by the t-test results showing a tcount value greater than ttable (19.295 > 1.667) and a significance value of 0.000, which is below the 0.05 threshold, indicating a significant relationship.